Research on factors that affecting late retirement age in public sector / Fatin Amisha Kamal and Noor Azahani Sulaiman - Kamal, Fatin Amisha; Sulaiman, Noor Azahani (Faculty of Business and Management, 2013)
The purpose of the research paper is to investigate the factors that affecting late retirement age in public sector. This study focused on the three factors that had been chosen as the variable that affecting the late retirement age which are Talent Shortage, Ageing Population and Gross Domestic Product. This research has been chosen the respondent from two organizations which are Majlis Sukan Negara (MSN) and Pejabat Pelajaran Daerah Kuala Langat (PPDKL). The findings will help to gain awareness and new ideas related to late retirement in order to overcome the woes towards public sector in Malaysia in order to achieve the vision and mission of their organization itself. The researchers were analyzing the findings and interpret data by Statistical Package for Social Science (SPSS) 20.0 version. As the result from this study, the researchers have found that there is significant relationship between Gross Domestic Product and Retirement Age. However, there is no significant relationship between Talent Shortages and Ageing Population toward Retirement Age.